Procurement Management Strategy for Zinc Ingots Based on LME Price Volatility: Achieving Cost Reduction Targets and Optimizing Operational Performance in the Hot-Dip Galvanizing Industry - Suherman; Nurhidayah; Abdullah Syakur Novianto (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of London Metal Exchange (LME) Zinc price volatility and Zinc Ingot procurement management strategies on the company's operational performance through procurement cost efficiency at the participating EPC company. High volatility in global Zinc prices can influence raw material procurement costs and consequently affect the effectiveness of operational performance. Therefore, appropriate procurement strategies are required to control costs and maintain operational efficiency. This study employed a quantitative approach using a survey method, with data collected through questionnaires distributed to 32 respondents involved in the company's procurement, production, and operational activities. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that LME Zinc price volatility significantly affects procurement cost efficiency and the company's operational performance. Zinc Ingot procurement management strategies also have a significant effect on procurement cost efficiency and operational performance. Furthermore, procurement cost efficiency significantly influences operational performance. The mediation analysis reveals that procurement cost efficiency successfully mediates the effects of both LME Zinc price volatility and Zinc Ingot procurement management strategies on operational performance. These findings suggest that effective commodity price risk management and procurement strategies are essential for improving cost efficiency and supporting the achievement of sustainable operational performance